Pengaruh Kualitas Pelayanan Pass Bandara Online Terhadap Perilaku Penyimpangan Pelayanan Di Kantor Otoritas Bandar Udara Wilayah III Surabaya - Titisan, Oral Fyat (CV. Kalimasada Group, 2023)
Public services are inseparable from the interaction between officers and service users, the change in the quality of airport pass services in the digital era which was previously carried out offline to online makes the interaction between officers and service users less. This study aims to determine whether or not there is an effect of the quality of airport pass services in the digital era on deviant behavior at the Airport Authority Regional III Surabaya and if so, what is the percentage of influence. This study employed quantitative methods using questionnaries as the data collection technique. with a sample size of 112 people obtained using the slovin formula. Data analysis using simple linear regression test, t test and coefficient of determination test. The results of this study indicate that there is an effect of the variable quality of airport pass services in the digital era as indicated by the Sig value. 0.00 in the T test. The amount of influence between the variable quality of airport pass services in the digital era on deviation behavior is 79.1%